Actuation and control of wing warping via tendon-sheath mechanism for flexible membrane wing mini-UAV - Lee, Shian (2018)
Unmanned Aerial Vehicles, also known as drones are very suitable and efficient for border patrol and surveillance missions. No human pilot is being put at risk, but they are usually not fully utilized due to the costs and operational difficulties. The introduction of the mini-UAV, which is much less expensive and also easier to operate, can minimize losses even if the aircraft perishes during the mission. However, given the frequent gusty conditions in lower altitudes, the mini-UAV can be difficult to maneuver. The flexible membrane wing (FMW) developed in this thesis helps to mitigate the effects of the gusts with the adaptive washout effect. Additionally, the FMW provides the convenience of quick deployment and storage by being foldable along the fuselage. This thesis details the research to achieve more roll control authority while preserving the adaptive washout and also foldable feature. A novel method of wing warping was discovered, which relies on the tendon-sheath mechanism. The nonlinearities of the tendon-sheath mechanism (TSM) actuated wing warping were identified and then modeled using a modified General Bouc-Wen (GBW) model for hysteresis. The parameters for the modified GBW model was found by utilizing optimization methods. A TSM wing warping controller, which is the main contribution of this thesis, was designed with a feed-forward and feedback control. The comparison between open loop and closed loop wing warping is shown. A significant improvement in warping accuracy was achieved in the closed loop system and is documented in the thesis. Further verifications such as computational fluid dynamic simulations, wind tunnel tests and flight tests were conducted to show the robustness and real world usability of the TSM wing warping controller on the FMW mini-UAV. This thesis has demonstrated the feasibility of the TSM wing warping roll control on the FMW mini-UAV while keeping the adaptive washout mechanism and the foldability of the FMW for storage purposes.